The Presentation of Proper Indicators for Evaluation of WHO Collaboration Centres' Activities in Iran - S Motevallizadeh Ardakani; SH Zakiani (Tehran University of Medical Sciences, 2012)
Background: There are thirteen WHO collaborating centres in Iran which no mechanism or model has ever been foreseen for the evaluation of them. This original research is innovative in Iran, which has been offered by the researcher through a joint research project with WHO. Methods: The aforesaid model has been approved by the International Relation Department of Ministry of Health& education. This was done to develop model and indicators for evaluation of WHOCC's activities in Iran, which includes online survey, reports, literature reviews and website searches, published literature in another country, documents in Undersecretary for Research and Technology of Iranian Ministry of Health and Medical Education. Results: We studied collaboration centres in other countries and then compared these indicators together and presented a proper indicators for evaluation of WHOCC' activities in Iran. Conclusion: Evaluation of WHOCC's activities could be used as a mean for implementing policies and promoting knowledge production. Evaluation of WHOCC' activities is country's requirements.